Pengaruh Penggunaan Media Sosial Dan Faktor Gaya Kepemimpinan Terhadap Pencapaian Tujuan Usaha Mikro Di Kota Depok - Muhammad Daffa Putra Mahmudi; Maulina Pia Wulandari; Fitria Avicenna (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2022)
Micro-businesses have the largest number of entrepreneurs (98,67%) among the total number of businesses in Indonesia and play a crucial role as the driving force of the country’s economy. However, the Covid-19 pandemic that has hit Indonesia has had a significant negative impact, including on the economic sector. Around 82,9% of micro, small and medium enterprises (MSMEs) have experienced negative effects during the pandemic, with a decline in revenue of over 30%. Therefore, in order for micro-businesses to recover from the pandemic’s impact, their performance needs to be improved to achieve business goals. The purpose of this study is to examine the influence of social media usage and leadership style factors on the achievement of micro-business goals in Depok city. This study utilizes a quantitative research approach with a causal survey design. The research sample consists of 340 participants selected through purposive sampling. The sample includes micro-business owners who have participated in the New Entrepreneur program in 2022 and were selected through questionnaire completion. Hypothesis testing using SPSS programming is employed as the research design. The result of this study indicate that social media usage and leadership style factors have a positive and significant influence on the achievement of micro-business goals, both partially and simultaneously. The research suggests that micro-business owners should maximize the use of social media to manage customer databases and enhance their influence in business leadership. Additionally, it is recommended that the Depok City Government supports micro-businesses through training and development activities